Integration of Noble Values in Tiban Art in Transformative Social Studies Learning - Mufid, M. Khoirul Annas Waladul; Turhan Yani , Muhammad; Sarmini,; Suprijono , Agus; Jefferi bin Haji Mat Lazim , Mohamed (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2024)
Local wisdom is an issue that is now widely discussed to integrate into learning including social studies learning. Tiban is one of the arts in East Java which has noble values ​​that can be integrated into social studies learning. This research aims to analyze how to integrate local wisdom in the art of Tiban in social studies learning using a PjBL model. This research used a qualitative approach using literature study methods. Data collection was carried out with the help of search engines. Articles were selected based on the suitability of the theme with a time limit starting from 2019 to 2023. The results were then analyzed using thematic analysis. The study results show that Tiban arts has many noble values that can be integrated into social studies learning include 1) divinity/religiousness, 2) humanity, 3) unity, and 4) deliberation. Integrating these noble values could be used in several philosophical foundations. Coupled with PjBL, it can incorporate process skills. So, transformative social studies learning uses a PjBL model, providing cognitive knowledge and transformation in attitudes and life skills. The results of this research can be used as a basis for developing social studies learning designs that integrate noble values through PjBL